Antisense-mediated exon skipping: A therapeutic strategy for titin-based dilated cardiomyopathy - Gramlich, Michael; Pane, Luna Simona; Zhou, Qifeng; Chen, Zhifen; Murgia, Marta; Schoetterl, Sonja; Goedel, Alexander; Metzger, Katja; Brade, Thomas; Parrotta, Elvira; Schaller, Martin; Gerull, Brenda; et al. (Embo Molecular Medicine, 2015)
Frameshift mutations in the TTN gene encoding titin are a major cause for inherited forms of dilated cardiomyopathy (DCM), a heart disease characterized by ventricular dilatation, systolic dysfunction, and progressive heart failure. To date, there are no specific treatment options for DCM patients but heart transplantation. Here, we show the beneficial potential of reframing titin transcripts by antisense oligonucleotide (AON)-mediated exon skipping in human and murine models of DCM carrying a previously identified autosomal-dominant frameshift mutation in titin exon 326. Correction of TTN reading frame in patient-specific cardiomyocytes derived from induced pluripotent stem cells rescued defective myofibril assembly and stability and normalized the sarcomeric protein expression. AON treatment in Ttn knock-in mice improved sarcomere formation and contractile performance in homozygous embryos and prevented the development of the DCM phenotype in heterozygous animals. These results demonstrate that disruption of the titin reading frame due to a truncating DCM mutation can be restored by exon skipping in both patient cardiomyocytes in vitro and mouse heart in vivo, indicating RNA-based strategies as a potential treatment option for DCM.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dilated cardiomyopathy; Exon skipping; Induced pluripotent stem cells; Titin